Self-regulation of effort for a better health-related quality of life: a multidimensional activity pacing model for chronic pain and fatigue management - Ioulia Barakou; Katie L. Hackett; Tracy Finch; Florentina Johanna Hettinga (Annals of Medicine, 2023)
AbstractPurpose To propose a comprehensive multidimensional model of activity pacing that improves health-related quality of life and promotes sustained physical activity engagement among adults with chronic conditions.Materials and methods A narrative review was conducted to examine the existing literature on activity pacing, health-related quality of life, pain and fatigue management, and physical activity promotion in chronic conditions.Results The literature revealed a lack of a cohesive approach towards a multidimensional model for using activity pacing to improve health-related quality of life. A comprehensive multidimensional model of activity pacing was proposed, emphasizing the importance of considering all aspects of pacing for sustained physical activity engagement and improved health-related quality of life. The model incorporates elements such as rest breaks, self-regulatory skills, environmental factors, and effective coping strategies for depression/anxiety. It takes into account physical, psychological, and environmental factors, all of which contribute significantly to the enhancement of health-related quality of life, physical function, and overall well-being, reflecting a holistic approach.Conclusions The model offers guidance to researchers and clinicians in effectively educating patients on activity pacing acquisition and in developing effective interventions to enhance physical activity engagement and health outcomes among adults with chronic conditions. Additionally, it serves as a tool towards facilitating discussions on sustained physical activity and a healthy lifestyle for patients, which can eventually lead to improved quality of life.